Measuring the Efficiency of BAZNAS in Managing Zakat Funds with Stochastic Frontier Approach Analysis, 2002–2016 - Risanda A.; Faishol Luthfi; Sri Herianingrum (International Journal of Zakat, 2018)
This study aims to measure the technical efficiency and identify factors that cause technical inefficiency of Badan Amil Zakat Nasional (BAZNAS) in managing zakat funds on receipt and the distribution of zakat funds. The data used were time series data from 2002 to2016. The input variables used were total assets and operational costs, while the output variables were the receipt of zakat funds and the distribution of zakat funds. Using stochastic frontier analysis, this study has successfully identified that total assets and operational costs had a positive and significant effect on the receipt of zakat funds. The same results also demonstrated that the operational costs for the distribution of zakat funds had a positive and significant effect. The results for total assets on distribution of zakat funds were positive but not significant. Overall, the technical efficiency regarding the receipt of BAZNAS zakat funds was found to be 94.98 percent, which means that there is 5.02 percent remaining that could still be optimized, while technical efficiency regarding the distribution of BAZNAS zakat funds was found to be 70.99 percent, leaving 29.01 percent that could still be optimized. Keywords: Badan Amil Zakat Nasional (BAZNAS), Stochastic Frontier Analysis, Technical Efficiency